Concepções de professores expressas nos conteúdos e nas metodologias propostas para o ensino e aprendizagem da matemática na 1ª e 2ª etapas da Educação de Jovens e Adultos em escolas municipais de Cuiabá-MT - Vanin, Letícia (2012)
The work presented attends a master`s degree research that had the main purpose on investigate and understand what are the conceptions that reveals the contents and the methodologies proposed by teachers that teach Math in the 1st and 2nd Stages for Young and Adults at Public Schools of Cuiabá-MT. The research was directed by the following question: which conceptions reveal the scholars documents and the teachers’ speech about the subjects and the approaches and methods in Math the 1st and 2nd Stages for Young and Adults at Public Schools of Cuiabá-MT? Considering the main nature of this research, the investigation methodology adopted was the qualitative approach of interpretation, in which we substantiate in Bogdan and Biklen (1994), Bourdieu (1997), Baraldi (1999), Furasté (2008), Triviños (1987) and Fiorentini and Lorenzato (2006). The research performed in two moments: in the first one we did a resurgence of Brazilian research that discuss Math teaching in the First Stage for Young and Adults, expecting to know the authors that discuss the Math Education in EJA to help us to build conceptual categories related to Young and Adults and to Math teaching. Thus, the theoretical basis of this work on the Young and Adult Education consists of Arroyo (2007), Brasil (1997), Cuiaba (2010), Darsie (1999), Di Pierro (2005), Fonseca (2005, 2007) Freire (1989, 2000), Gadotti (1996, 2001), Haddad (2003), Haddad and Di Pierro (2000), Ribeiro (2001), among others. In relation to mathematics education, used to enrich our thinking, theorists, Ausubel et al (1980), Bassanezi (2002), Brasil (2001), Borba (1999, 2001), Burak (1987, 1998), Coll (1999), D 'Ambrosio (1991, 1996, 1998, 2005, 2007) and Darsie (1998, 2001), Fonseca (2005, 2006, 2007) and Fiorentini (1995), Freire (1983), Grando (1995, 2000), Huizinga (1971 ), Michael and Miorim (2004), Brasil (1997), among others. From the mentioned material and data collected we used as analyzing categories, the Bank and Emancipating of Education. The second moment of our investigation was made a field research with four teachers that manage Math in two schools for 1st and 2nd Stages for Young and Adults at Public Schools of Cuiabá-MT, named to this work as Caju and Bocaiúva School. As instruments to collect data we made written questions, analyses and interviews. The importance of this research is, mainly, to look up for paths that reveals the most enlightening on how does the organization process of control subjects worked in class with students from the 1st and 2nd degrees of EJA. Answering to the question of this work investigation, we can tell that, the analysis says that both categories we chose as reference to this research, were adopted by the teacher, or in other words, Bank and Emancipatory. However, we notice a bigger contact with the conception Bank Education.